The Relevance of Philosophical Thinking in Solving Problems - Fatma Husna Haibah Nurullah; Maspuroh; Hasbi Isnaeni; Ingeu Siti Aisyah (Demagogi: Journal of Social Sciences, Economics and Education, 2025)
This research aims to understand the relevance or relationship of philosophical thinking in solving problems. The method used in this study uses a descriptive qualitative research type. Data comes from the library research method or approach which is carried out by searching for primary and secondary data sources in literature reviews. The results of the study with a philosophical way of thinking mean that a problem that arises should not be solved with hasty or hurried steps. However, we must first think about the problem before we solve it. Starting from the root of the problem, solving it systematically, looking from a holistic perspective and seeking the truth of the solution to a problem. So philosophical thinking is able to make humans solve problems by thinking radically, systematically, universally, and speculatively in guiding humans to think more critically, more deeply, and further in seeing reality in order to gain clarity or explanation of all reality.